Bone health and SATB2‐associated syndrome. Issue 3 (27th December 2017) - Zarate, Y.A.; Steinraths, M.; Matthews, A.; Smith, W.E.; Sun, A.; Wilson, L.C.; Brain, C.; Allgove, J.; Jacobs, B.; Fish, J.L.; Powell, C.M.; Wasserman, W.W.; et al.
Abstract : SATB2 ‐associated syndrome (SAS) is a rare disorder caused by alterations in the special AT‐rich sequence‐binding protein 2 ( SATB2 ). Skeletal abnormalities such as tibial bowing, osteomalacia, osteopenia or osteoporosis have been reported suggesting a higher frequency of skeletal complications in SAS. The optimal timing, necessity, and methodology for routine assessment of bone health in individuals with SAS, however, remain unclear. We report molecular and phenotypic features of 7 individuals with SAS documented to have low bone mineral density (BMD) ascertained by dual‐energy X‐ray absorptiometry (DXA), often preceded by tibial bowing. The lowest BMD Z‐scores ranged −2.3 to −5.6. In 4 individuals, total alkaline phosphatase levels were elevated (2 with elevated bone fraction) around the time of low BMD documentation. A clinically significant fracture history and a diagnosis of pediatric osteoporosis were present in 4 individuals. Pamidronate treatment in 2 children improved BMD. In conclusion, low BMD, fractures, and tibial bowing are relatively common skeletal complications in individuals with SAS. DXA is a useful tool when evaluating a child with SAS suspected to have low BMD and the results might alter clinical management. Abstract :